Effect of Mobile Use on Reaction Time - Chinmay Shah; P A Gokhale; H.B. Mehta (Al Ameen Medical College, 2010)
The use of cellular phones has skyrocketed in recent years, with more than 118 million subscribers in the United States as of July 1, 2001. Recent estimates suggest that cell phone users spend 60% of their cell phone time while driving. Reaction time is one of the important methods used to study a person's central information processing speed and fast coordinated peripheral movement response. The purpose of this study was to compare the reaction time without mobile use and with mobile use. It can be concluded that the reaction time is a prolonged with mobile use. The results of the study that has been described carry two significant implications for use of cellular phones. First, all users of cellular phones should be advised not to engage in intense phone conversations while the vehicle is moving. Businesses whose employees regularly carry on transactions by means of cellular phones might advise, or even direct that protracted dealings over the phone be avoided while the vehicle is underway.